A systematic review of interventions to reduce psychological distress in pediatric patients receiving radiation therapy. Issue 2 (February 2019) - O'Connor, Moira; Halkett, Georgia KB
Highlights: Anxiety leading to movement may result sedation during pediatric radiotherapy. We need theory driven interventions to reduce pediatric patients' anxiety and distress. Cognitive behavioural approaches child development and preparation via therapeutic play may be useful. Abstract: Objective: Radiation therapy (RT) is a cornerstone for management of pediatric cancer. For younger patients, unintended radiation to critical organs is a concern and children need to remain immobile. Distress in children is common so many centres sedate pediatric patients. Children often are unable to remain still, due to anxiety. Interventions to reduce distress could also reduce sedation rates. The objectives of this systematic review were to: review the interventions used to address pediatric RT patients' distress and anxiety and assess their effectiveness. Methods: A systematic search of qualitative and quantitative studies from 1996 to 2016 was conducted using PRISMA guidelines. Nine articles were identified for inclusion in the final review. These articles were reviewed using a quality rating. Results: Participants included patients 19 years of age or younger, parents and RTs. All were single-site studies. Five studies had a control group, 3 studies had no control group, and 1 study was qualitative. Quality was not high. Six studies reported significant effects. Only one study reported group differences in children's reported anxiety. Conclusion: Cognitive behavioural approaches appear to be worth exploring further, as are approaches grounded in child development. Therapeutic play, particularly procedural preparation via play, also seems to be a useful starting point.